2021
DOI: 10.1111/pai.13479
|View full text |Cite
|
Sign up to set email alerts
|

Exercise‐induced allergic reactions after achievement of desensitization to cow's milk and wheat

Abstract: Background We have previously reported that more than half of the patients who achieved desensitization after wheat rush oral immunotherapy (OIT) developed exercise‐induced allergic reaction on desensitization (EIARD). However, data on EIARDs after slow OIT are lacking. Therefore, this study aimed to investigate the results of exercise provocation tests (EPTs) in patients after slow OIT for cow's milk and wheat allergies. Methods This was a retrospective chart review of 87 EPTs in 74 patients. The EPTs were pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…In cases that already experienced food-induced allergic symptoms, FDEIA with strict definition has not been diagnosed even if exercise after food ingestion causes anaphylaxis. Kubota et al [ 10 ] reported that exercise-induced allergic reactions were observed after slow OIT for cow’s milk and wheat. Exercise-induced allergic symptoms in children with food allergies in this study should be called exercise-induced allergic reaction rather than FDEIA.…”
Section: Discussionmentioning
confidence: 99%
“…In cases that already experienced food-induced allergic symptoms, FDEIA with strict definition has not been diagnosed even if exercise after food ingestion causes anaphylaxis. Kubota et al [ 10 ] reported that exercise-induced allergic reactions were observed after slow OIT for cow’s milk and wheat. Exercise-induced allergic symptoms in children with food allergies in this study should be called exercise-induced allergic reaction rather than FDEIA.…”
Section: Discussionmentioning
confidence: 99%
“…A study evaluating the two-year follow-up prognosis for WA patients who achieved short-term SU after receiving wheat OIT revealed six out of eight symptomatic patients experienced adverse allergic reactions after exercise and three of them developed anaphylaxis [85]. Studies reported that EIARDs occurred not only after rush OIT but also after slow OIT for wheat, with 66.7% (14/21) and 48.4% (15/31) of WA patients developing EIARDs respectively [86,87]. Therefore, exercising after wheat intake may be the primary trigger for allergic symptoms during or after OIT.…”
Section: Precautions For Oitmentioning
confidence: 99%
“…Interestingly, among the patients who were positive for EIARD and who underwent a second EPT, the EIARD disappeared in four of six participants. 14 Also, a retrospective study conducted in Japan showed that, after WOIT, 25% of the subjects (6/24) had a positive EPT result; one subject required treatment with epinephrine. 15 Taken together, results of these studies suggest that consideration of an EPT before liberalizing exercise restrictions may be important for patients undergoing WOIT.…”
Section: Specific Challenges and Considerationsmentioning
confidence: 99%